مسند امام احمد میں مباحثِ سیرت کا تحقیقی جائزہ: Research Review of the prophet Sirat Collection in Musnad Imam Ahmad - Hafiz Mubashir Rasheed; Dr Hafiz Qudratullah (International Research Journal of Arabic and Islamic Studies, 2024)
The main sources of Islam are two: the Qur'an and the Hadith. This shows the importance of hadith. And The religion of Islam is the name of divine revelation, and there are two types of revelation, and hadith is also a part of divine revelation. The words sirat and hadeeth have many meanings in common, while in many places they also have different meanings. And The position of Musnad Imam Ahmad in various books of Hadith is very prominent and prominent, which is also authentic and reliable. Musnad Ahmad is an important repository of Hadith in terms of its comprehensiveness, so he is also the marja'a of Muhaddiths (Ahl-e-Hadith). And Musnad Ahmad is a comprehensive book of hadith as well as an authentic source of the Prophet Seerat. Musnad Ahmad also contains comprehensive hadiths about the life of the Prophet (peace and blessings of Allaah be upon him). And Musnad Ahmad's collection of sirat-e-nabawi is more reliable than the historical books. Musnad Ahmad's narrations will be a great addition to the discussion of seerat-e-nabawi. ﷺMusnad Ahmad is a book collecting and covering the topics of seerat.